THE EFFECT OF USING FLASHCARD ON STUDENTS’ WRITING ABILITY IN THE DESCRIPTIVE TEXT OF THE TENTH GRADE STUDENTS AT SMA SWASTA HARAPAN BANDAR PULO BATANG SERANGAN - Wiki Fadillah; Nudia Yultisa; Syahran Yusuf (Serunai : Jurnal Ilmiah Ilmu Pendidikan, 2022)
This Research was conducted for the tenth grade students of SMAS Harapan Bandar Pulo. The total population was 59 then the writer got 26 students as the research sample. The research used one group pre-test and post-test design. Based on the students’ problems in writing before got treatment using Flashcard, students confused to write ideas, students couldn’t develop the paragraph and habitually wrote text in wrong sentence pattern and grammatical error. After conducted the flashcard as the media to study in looking at pre-test and post-test score, the result of the data revealed after using flashcard, the students’ writing score were higher. It was proved in looking at the mean score pre-test (43) and post-test (78). Then after calculated the data, it stated that the value of t-test was 24,64. The degree of freedom (df) is 25 (df = . In looking at the t-table, in df 25 showed that the value of t-table ( was 2,06 for 5% and 2,79 for 1%. The result was proved if the t-test was higher that t-table (24,64 > 2,06). Therefore, the writer concluded that the alternative hypothesis was accepted. The alternative hypothesis declared that there was a significant effect of using Flashcard on students’ writing ability in descriptive text. After having the t-test result, it realized that flashcard gave positive impact. Flashcard helped students to creat ideas, to develop the paragraph and to write the text in correct form.